MEASURMENT ECONOMIC AND MARKETING EFFICIENCY FOR CUCUMBER GROWING IN GREEN HOUSES SHATRAH AT DHIQAR PROVINCE IRAQ DURING PLANTING SEASON 2017 - Mahmood, Z. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study  was aimed to measure the production efficiency, cost efficiency, profit-maximizing production level, and net income at actual, cost-minimizing, and profit-maximizing production, as well as to calculate the minimum priced accepted by cucumber producers to supply their products, estimate supply function for cucumber producers, estimate the marketing efficiency of cucumber grown in greenhouses. A random sample of 45 cucumber growers from Dhi Qar governorate, Al-Shatra district/ Iraq during the agricultural season 2017 was selected. Due to its harmony with economic and statistical logic, cubic formula was used to estimate the cost function. Results showed that the optimal production of cucumber was 59.54 tons, and the efficiency percentage at the actual production size was 0.53. Price elasticity was about 0.24 at the minimum price accepted by the producers (127.78 dinars) to supply their products. That means when the farm prices increase by 10%, the quantity offered in the market increased by 2.3%.  Cost efficiency was 1.5, while profit-maximizing production size in short-term was 77.44 tons. The net income for actual, cost minimizing and profit maximizing production were 10725.4 dinars, 16471.99 dinars and 19189.7 dinars respectively. Furthermore, the study revealed a marketing efficiency of 91.6%, which is a good indicator for marketing performance. Based on these results, the study recommends for adapting a production policy aiming at optimizing the use of available resources and improving the efficiency of cucumber production.